ANALISIS KINERJA WAKTU DAN BIAYA MENGGUNAKAN METODE EARNED VALUE PADA PROYEK X DI JAWA BARAT - Cintri Anjani Rahmada Putri (LPPM Politeknik Astra, 2023)
Project control is a very important function in implementing a construction project. In project implementation, there may be delays, acceleration, or in accordance with the project plan schedule. Delays or acceleration of projects can provide advantages or disadvantages. One method that can be used to avoid losses in a project is to use the earned value method. This method involves the use of cost budget plans, unit price analysis and project progress reports to obtain BCWS (Budgeted Cost of Work Schedule), BCWP (Budgeted Cost of Work Performance), and ACWP (Actual Cost of Work Performed). Research begins with collecting data, carrying out analysis, and concluding the results from the collected data. The purpose of this research is to estimate the time and costs that will be required and to project the costs and time required to complete the project. From the calculation results of applying the earned value method, it is known that the results of the review up to the 40th week showed that the BCWS value = Rp. 172,020,918,000.- ; BCWP = Rp. 147,714,360,000.-; ACWP = Rp. 120,240,052,674.-, while the schedule variance value up to week 40 is negative and the cost variance value is positive. For the calculation results, the estimated final completion time is 56 weeks with an estimated completion time of 54 weeks and the calculation results estimate the final completion cost of Rp. 186.130.112.499.- with a planned budget of Rp. 206,000,000,000.00. From the results it is known that the work was late but experienced cost savings.